Inclusive education: building together towards intercultural citizenship - Morales Acosta, Gina Viviana; Valenzuela Yañez, Fanny; Roblero González, Carla (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: to describe elements of the construction of intercultural citizenship for sons and daughters of migrant parents that contribute to an inclusive education in Chile. Originality/support: It problematizes the inclusion of schoolchildren in the context of migration in relation to the protection of their rights, the positioning of interculturality in Chile and the school as a space for the formation of possible citizenships. Method: Documentary review of the state of the art. Strategy/ information gathering: Consultation in academic databases, direct request for bibliography and documents to experts and/or researchers on the subject and search by subject in the Library of the National Congress of Chile. Conclusions: the importance of the curriculum as a reference where the recognition of the existing diversity in the classroom can be concretized and therefore the promoter for the symmetrical and respectful dialogue with the diverse cultures that inhabit the country and that form an intercultural citizenship is revealed